Axenizing and Culturing Endomigratory Plant-Parasitic Nematodes using Pluronic F127, Including its Effects, on Population Dynamics of Pratylenchus penetrans - Ko, M P (Journal of nematology, 1996)
A non-chemical technique for surface sterilizing plant-parasitic nematodes for aseptic cultures is described. The method is most applicable to nematodes with active migratory infective stages and requires only a few starting specimens. Rate of achieving a primary aseptic culture with the technique ranged from 60%-100% depending on the conditions of the specimens collected for culturing. Aseptic cultures of species of Meloidogyne, Rotylenchuluz, Pratylenchus, and Radopholus initiated with the method remained contamination-free after 12 months of maintenance in tomato root explant or alfalfa callus cultures. Further studies of Pluronic F127, a polyol gel medium employed in the technique to confine the spread of contaminating bacteria or fungi associated with the nematodes, showed that the polyol gel was a suitable support medium for culturing corn root explant, alfalfa callus tissues, and consequently Pratylenchus species including P. agilis, P. brachyurus, P. scribneri, and P. penetrans. During the course of 10 months, P. penetrans reared in polyol-base medium followed a standard biological growth curve, multiplied to a higher population density, maintained a similar female-to-male ratio, and possessed a similar tendency to reside inside or outside host tissues as did P. penetrans reared in agar-base medium. The percentages of P. penetrans juveniles in the sub-populations residing outside or inside the host tissues reared in polyol-base medium also were similar to and fluctuated temporally in like manner as those reared in agar-base medium. Members of these sub-populations from the polyol- or agar-base were equally infective and reproductive after 9 months of culturing